Миграционная структура населения Валковского района Харьковской области по данным о квазигенетических маркёрах - Горпинченко, М.Ю.; Утевская, О.М.; Атраментова, Л.А. (Фактори експериментальної еволюції організмів, 2013)
Aims. To study the migration structure by surnames used as quasigenetic markers. Methods. Totally 30,447 peoples and 2375 surnames were analyzed. The interpopulation quasigenetic distancies were calculated by surnames frequencies. The association between the geographic and quasigenetic distancies was estimated by the Mantel test. The ethnicity was analyzed for the 100 of most common surnames. Results. The correlation coefficient between geographic and quasigenetic interpopulation distances was not statistically significant (r = 0.017, p> 0.05). About 63 % of the analyzed surnames have Ukrainian origin, 14 % – Slavonian, 5 % – Belarusian, 3 % – Russian and 2 % – Turkic. Conclusions. Surnames, as quasigenetic markers, reflect the migration processes in the study area, i.e. the early colonization of the region by migrants from theWestern Ukraine and the intensive intraregional migration leading to the genetic homogeneity of the populations.

Key words: surname, migration, quasigenetic markers, etnomarkery, Kharkiv region,Ukraine.